Dynamics of the Application of the Percentage of Vote Difference in the Resolution of Disputes Over the Results of Local Head Elections - M. Abdim Munib; Yayuk Dwi Agus Sulistiorini (Universitas Negeri Malang, 2025)
The objective of this study is to analyze the formal requirements for filing a petition to annul the results of regional head elections and to examine the issues surrounding the application of the vote margin threshold in resolving disputes over regional head election results. This study employs a normative legal research method, using a statutory, conceptual, and case approach. The findings indicate that a petition for the annulment of regional head election results must satisfy two requirements, namely the existence of discrepancies in vote calculations between the election organizers and the petitioner, and the fulfillment of the vote margin threshold ranging from 0.5 percent to 2 percent as stipulated in Article 158 of Law Number 10 of 2016. The implementation of simultaneous regional head elections from 2015 to 2024 has generated a significant number of disputes totaling 743 registered cases. The Constitutional Court has demonstrated inconsistency in applying the vote margin threshold, as 24 out of 181 accepted cases did not meet the required percentage. The Constitutional Court's decision to accept cases that failed to meet the vote margin threshold is considered to deviate from the principle of legal certainty.